A Novel Technique for Varus Tibial Cutting for Oxford Unicompartmental Knee Arthroplasty - Hiranaka, Takafumi (Clin Orthop Surg, 2020)
To reduce the stress on the medial tibial cortex and to decrease the risk of fracture, a varus cut of the tibia appears to be a reasonable alternative to the orthogonal cut by conventional methods. We present a new instrument and procedure, which enables a varus tibial cut for Oxford unicompartmental knee arthroplasty. We used a custom-made, slidable fixator instead of the standard fixator to set the extramedullary rod on the leg. We also made a numeric formula and a chart to arrange the varus cutting angle using the length of the mediolateral shift of the distal end and the longitudinal extension length of the extramedullary tibial rod. A varus cut up to 4.5° can be controlled. This technique is a simple and useful means of obtaining a varus tibial cut for Oxford unicompartmental knee arthroplasty.